The Two and Three Electrodes Systems Topology Optimization of Electrochemical Sensors (Texas Journal of Engineering and Technology, 2024)
Miniature electrochemical sensors can be produced using thick film technology. Fabrication technology optimization of thick-film sensors, the adjustment of optimal technological properties and especially the optimal properties of thick-film electrode materials and electrode topology are main problems of sensor design. The electrodes topology design represents one of very important parts. It is very complicated, because of many contradictory requests that must be solved. Some aspects about this problem in electrochemical sensor area are discussed in this paper.